Preparation method of double-perovskite type solid electrolyte and all-solid-state battery
Through the preparation method of the double perovskite solid electrolyte, the ion conductivity of the electrolyte is improved and the sensitivity to moisture and air is reduced, and the problems of unsatisfactory ion conductivity and sensitivity to moisture are solved. It is suitable for all-solid state batteries with high energy density.
Patent Information
- Application Number
- CN202510005532.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
AI Technical Summary
The ionic conductivity of halide solid electrolyte is not ideal, and it is very sensitive to moisture, making it difficult to meet the requirements of high energy density.
The preparation method of the double perovskite solid electrolyte is adopted to synthesize the base material of the double perovskite A2B(I)B(II)X6, and mix the lithium salt, solvent and the base material through ion exchange method to prepare the double perovskite solid electrolyte.
It significantly improves the ionic conductivity of the double perovskite solid electrolyte and reduces the sensitivity to moisture and air. It is suitable for use in all-solid state batteries with high energy density.
Smart Images

Figure CN119797415A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid electrolytes, and in particular to a preparation method of a double perovskite solid electrolyte and an all-solid-state battery. Background Art
[0002] With the continuous development of energy technology, liquid electrolytes have been continuously developed due to their many advantages such as high ionic conductivity, good compatibility with electrodes, and good electrochemical stability. However, liquid electrolytes are often organic, which makes them flammable, unsafe, and have serious dendrite problems, making it difficult to meet the requirements of high energy density. In order to solve this problem, the use of solid electrolytes to prepare all-solid-state batteries is widely considered to be a very promising approach.
[0003] At present, solid electrolytes for all-solid-state batteries are mainly divided into three types: oxide, sulfide and halide solid electrolytes. Among them, halide solid electrolytes have attracted much attention because of their advantages such as better ionic conductivity and interface contact compared to oxide solid electrolytes, and better air stability compared to sulfide solid electrolytes. However, the ionic conductivity of halide solid electrolytes is not ideal at present, and they are very sensitive to moisture. Therefore, the development of high-energy-density solid electrolytes still faces huge challenges. Summary of the invention
[0004] In view of the problem that the ionic conductivity of halide solid electrolytes is not ideal and they are very sensitive to moisture, the present invention provides a method for preparing a double perovskite solid electrolyte and an all-solid-state battery, which can improve the ionic conductivity of the double perovskite solid electrolyte; the obtained double perovskite solid electrolyte has significantly reduced sensitivity to moisture and air.
[0005] The technical solution adopted by the present invention to solve its technical problem is that the preparation method of the double perovskite solid electrolyte of the present invention first synthesizes the double perovskite A2B(Ⅰ)B(Ⅱ)X6 base material, and then mixes the required lithium salt, solvent and base material by ion exchange method to prepare the double perovskite solid electrolyte.
[0006] The specific steps include:
[0007] S1. The salts, denoted as AX, B(Ⅰ)X, and B(Ⅱ)X, are weighed in a molar ratio of 1.5-2.5:0.5-1.5:1 (preferably 2:1:1), mixed with an appropriate amount of water or HX solution, and heated and stirred at 50-220° C. for more than 15 minutes (preferably 20-30 minutes) to obtain a mixed solution;
[0008] Where A, B(Ⅰ), and B(Ⅱ) represent cations, respectively, and X represents anions;
[0009] S2, separating the mixed liquid obtained in step S1 by solid-liquid separation (preferably centrifugal separation), washing and drying to obtain a double perovskite-type substrate material A2B(Ⅰ)B(Ⅱ)X6;
[0010] S3, mixing the double perovskite substrate material A2B(Ⅰ)B(Ⅱ)X6 obtained in step S2 with a solvent and an excess of lithium salt, and heating and stirring for more than 48 hours to perform ion exchange;
[0011] S4, solid-liquid separation (preferably centrifugal separation), washing and drying to obtain a double perovskite solid electrolyte.
[0012] Preferably, in step S1, the anion X of the halide salt is a fluoride ion F - 、Chloride ion Cl - 、Br - 、Iodide ion I - 、cyanide ion CN - More preferably, the anion X of the halide salt is one of a fluoride ion and a chloride ion.
[0013] Preferably, in step S1, the cation in the halide salt AX is a potassium ion K + 、Rubidium ion Rb + , Cesium ion Cs + 、Silver ion Ag + 、Ti ion Ti 4+ 、Ammonium ion NH4 + 、Methylamine cation CH3NH3 + At least one of .
[0014] Preferably, in step S1, the cation in the halide salt B(I)X is a lithium ion Li + 、Sodium ion Na + Potassium ion K + 、Rubidium ion Rb + 、Silver ion Ag + 、Gold ion Au + 、Ti ion Ti 4+ 、Ammonium ion NH4 + At least one of .
[0015] Preferably, in step S1, the cation in the halide salt B(II)X is an aluminum ion Al 3+ 、Gallium ion Ga 3+ 、Indium ion In 3+ 、Ti ion Ti 3+ 、Antimony ion Sb 5+ 、Bi ion 5+ , at least one of transition metal elements.
[0016] Preferably, in step S1, the halide salts AX and B(I)X are halide salts of different types, but B(I)X and B(II)X may be halide salts of the same type.
[0017] Preferably, in step S1, the amount of HX solute in the HX solution is 10 times or more of the amount of double perovskite substrate material A2B(Ⅰ)B(Ⅱ)X6. In step S1, water is deionized water, and the amount used is 10 times or more of the amount of double perovskite substrate material A2B(Ⅰ)B(Ⅱ)X6.
[0018] Preferably, in step S3, the solvent is one of alcohol, ether, ester, amide, carbonate, sulfide, sulfoxide, sulfone, sulfonamide, nitrile, dinitrile, phosphate, sulfite, and sulfate. The selected solvent should be able to fully dissolve the lithium salt, but insoluble or slightly soluble in the double perovskite substrate material A2B(Ⅰ)B(Ⅱ)X6.
[0019] Preferably, in step S3, the anion of the lithium salt is at least one of bistrifluoromethylsulfonyl, bisfluorosulfonyl imide, hexafluorophosphate, hexafluoroborate, bisoxalatoborate, difluorooxalatoborate, fluorosulfonyl-trifluoromethylsulfonyl imide, bispentafluoroethanesulfonyl imide, perchlorate, trifluoropotassium sulfonate, nitrate, carbonate, sulfate, and chloride.
[0020] Preferably, in step S3, the amount of lithium salt is more than 1 times (preferably 5-8 times) the amount of double perovskite substrate material A2B(Ⅰ)B(Ⅱ)X6; the amount of solvent is more than 5 times (preferably 20-50 times) the amount of lithium salt.
[0021] Preferably, in step S3, the heating temperature is 50-220°C (preferably 80°C).
[0022] Preferably, step S3 and step S4 need to be performed in an argon environment, and the water oxygen is controlled below 0.2 ppm.
[0023] An all-solid-state battery comprises a double perovskite solid electrolyte prepared by the present invention.
[0024] The present invention has the following advantages:
[0025] 1) The present invention uses a double perovskite alloy as a base material, and the prepared solid electrolyte tends to retain the properties of the base material. The double perovskite base material has good stability, so the sensitivity of the solid electrolyte obtained in this way to moisture / air is significantly reduced.
[0026] 2) Solid electrolytes are prepared by ion exchange. Since there is a certain gap between the atomic radii of the exchanged elements, a larger diffusion channel is reserved for the exchanged atoms, which improves the ionic conductivity of the electrolyte.
[0027] 3) The preparation method of the present invention is simple, can synthesize solid electrolytes quickly and at low cost, has cheap process raw materials, good stability, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The XRD test results in Comparative Example 1 and Comparative Example 2 are shown in FIG.
[0029] Figure 2 are the SEM test results of Comparative Example 1 and Comparative Example 2, wherein ab is the SEM test result of Comparative Example 1, and cd is the SEM test result of Comparative Example 2;
[0030] Figure 3 are the SEM test results of Example 1 and Example 2, wherein ab is the SEM test result of Example 1, and cd is the SEM test result of Example 2;
[0031] Figure 4 These are the test results of ionic conductivity of solid-state batteries made of the solid-state electrolytes of Examples 1, 2, 3 and Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with specific embodiments.
[0033] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0034] Comparative Example 1
[0035] This comparative example comprises the following steps:
[0036] S1. Take 2 mmol of indium chloride InCl3 (0.4424 g), 4 mmol of cesium chloride CsCl (0.6734 g) and 2 mmol of sodium chloride NaCl (0.1169 g), add them together into 40 ml of concentrated hydrochloric acid (the mass concentration of concentrated hydrochloric acid is 36%), stir and heat at 80°C for 20 minutes to obtain a mixed solution;
[0037] S2. Pour the mixed solution obtained in step S1 into a centrifuge tube, balance it with anhydrous ethanol, and centrifuge it at 8000r / min to separate the solid and liquid; after centrifugation, pour out the liquid phase, add anhydrous ethanol to balance it, and centrifuge it again to separate the solid and liquid (this is a washing step, mainly to wash away the hydrochloric acid and unreacted raw materials); put the fully washed material into a vacuum box at 80°C and dry it for 10 hours. The obtained material is a double perovskite-type substrate material Cs2NaInCl6, which is represented as Cs2NaInCl6 (HCl) in this comparative example 1.
[0038] Comparative Example 2
[0039] This comparative example comprises the following steps:
[0040] S1. Take 2 mmol of indium chloride InCl3 (0.4424 g), 4 mmol of cesium chloride CsCl (0.6734 g) and 2 mmol of sodium chloride NaCl (0.1169 g), add them together in 40 ml of deionized water, and stir at 80°C until evaporated to dryness;
[0041] S2. Rinse the solid obtained in step S1 with anhydrous ethanol, and centrifuge at 8000r / min to separate the solid and liquid; pour out the liquid phase after centrifugation, add anhydrous ethanol to balance, and centrifuge again to separate the solid and liquid; put the fully washed material into a vacuum oven at 80°C and dry it for 10 hours. The obtained material is a double perovskite substrate material Cs2NaInCl6, which is represented as Cs2NaInCl6(H2O) in this comparative example 2.
[0042] Figure 1 The XRD curves of Comparative Examples 1 and 2 show that the main XRD peaks of Comparative Examples 1 and 2 are well matched with the standard PDF card. This shows that both methods can synthesize the target material, but Comparative Example 2 using deionized water as a solvent has certain impurity peaks, which is inferred to be because some unreacted substances are not washed away. However, the main peaks are all in agreement. This also shows that the synthesis of Comparative Example 2 is feasible, and also reflects that the material we synthesized has excellent water stability.
[0043] Figure 2 The SEM images of Comparative Example 1 and Comparative Example 2 show that the material synthesized in Comparative Example 1 has uniform particle size and good surface morphology. Comparative Example 2 shows a larger particle size and a wide particle size distribution, which is conducive to the improvement of compaction density, indicating that it is relatively rough and is conducive to ion passage.
[0044] Example 1
[0045] This embodiment includes the following steps:
[0046] S1. Take 2 mmol of indium chloride InCl3 (0.4424 g), 4 mmol of cesium chloride CsCl (0.6734 g) and 2 mmol of sodium chloride NaCl (0.1169 g), add them together into 40 ml of concentrated hydrochloric acid (the mass concentration of concentrated hydrochloric acid is 36%), stir and heat at 80°C for 20 minutes to obtain a mixed solution;
[0047] S2, pour the mixed solution obtained in step S1 into a centrifuge tube, balance it with anhydrous ethanol, centrifuge it at 8000r / min to separate the solid and liquid; pour out the liquid phase after centrifugation, add anhydrous ethanol to balance it, repeat the centrifugation to separate the solid and liquid; put the fully washed material into a vacuum box at 80°C and dry it for 10 hours, and the obtained material is Cs2NaInCl6;
[0048] S3, weigh 1 mmol of material Cs2NaInCl6 (0.6126 g), add 5 mmol of lithium bis(fluorosulfonyl)imide (LiFSI 0.9353 g), and 50 mmol of ethylene glycol dimethyl ether (DME, 4.506 g), mix, and heat and stir at 80°C for 48 hours;
[0049] S4, centrifuge and wash the material obtained in step S3 with ethylene glycol dimethyl ether DME, the centrifuge and washing operations are the same as the centrifuge and washing operations in step S2. Heat and dry the centrifuged material to obtain the final material double perovskite solid electrolyte, represented by Li x Cs 2-x NaInCl6(DME).
[0050] Operation steps S3-S4 need to be performed in an argon environment, and the water oxygen level is controlled below 0.2 ppm.
[0051] Example 2
[0052] This embodiment includes the following steps:
[0053] S1. Take 2 mmol of indium chloride InCl3 (0.4424 g), 4 mmol of cesium chloride CsCl (0.6734 g) and 2 mmol of sodium chloride NaCl (0.1169 g), add them together into 40 ml of concentrated hydrochloric acid (the mass concentration of concentrated hydrochloric acid is 36%), and stir and heat at 80°C for 20 minutes;
[0054] S2, pour the mixed solution obtained in step S1 into a centrifuge tube, and balance it with anhydrous ethanol; centrifuge at 8000r / min to separate the solid and liquid; pour out the liquid phase after centrifugation, add anhydrous ethanol to balance, and repeat the centrifugation liquid separation again; put the fully washed material into a vacuum box at 80°C and dry it for 10 hours, and the obtained material is Cs2NaInCl6;
[0055] S3, weigh 1 mmol of material Cs2NaInCl6 (0.6126 g), add 5 mmol of lithium bis(fluorosulfonyl)imide (LiFSI, 0.9353 g), and 50 mmol of dimethyl sulfoxide (DMSO, 4.506 g), mix, and heat and stir at 160°C for 48 hours;
[0056] S4, centrifuge and wash the material obtained in step S3 with DME (DME is used for washing here, mainly because DME is volatile and easy to handle), and the centrifugation and washing operations are the same as the centrifugation and washing operations in step S2; heat and dry the centrifuged material to obtain the final material double perovskite solid electrolyte, represented by Li x Cs 2-x NaInCl6(DMSO).
[0057] Operation steps S3-S4 need to be performed in an argon environment, and the water oxygen level is controlled below 0.2 ppm.
[0058] Figure 3 The SEM images of Example 1 and Example 2 are shown in Figure 1. The SEM images of Example 1 and Comparative Example 1 show that the surface of the material after ion exchange is rough, and there are many cavities on the surface of the original material, which is conducive to the adhesion between particles to provide a better compaction density. In the SEM of Example 2, it can be seen that the particles of the sample have coarser columnar particles, which is inferred to be caused by the agglomeration of particles in a certain crystal direction due to ion exchange, which also shows that the experiment successfully carried out ion exchange.
[0059] Example 3
[0060] This embodiment includes the following steps:
[0061] S1, take 2mmol bismuth bromide BiBr3 (0.8974g), 4mmol potassium bromide KBr (0.4760g) and 2mmol silver bromide AgBr (0.3755g), add them together into 40ml hydrobromic acid (mass concentration of hydrobromic acid is 48%), and heat at 120°C for 30 minutes;
[0062] S2, pour the mixed solution obtained in step S1 into a centrifuge tube, and balance it with anhydrous ethanol; centrifuge at 8000r / min to separate the solid and liquid; pour out the liquid phase after centrifugation, add anhydrous ethanol to balance, and repeat the centrifugation liquid separation again; put the fully washed material into a vacuum box at 80°C and dry it for 10 hours, and the obtained material is K2AgBiBr6K2AgAlI6;
[0063] S3, weigh 1 mmol of material K2AgBiBr6 (0.8745 g), add 5 mmol of lithium bis(fluorosulfonyl)imide (LiFSI, 0.9353 g), and 50 mmol of dimethyl sulfoxide (DMSO, 4.506 g), mix, and heat and stir at 160°C for 48 hours;
[0064] S4, centrifuging and washing the material obtained in step S3 with DME, the centrifuging and washing operations are the same as those in step S2; heating and drying the centrifuged material to obtain the final material double perovskite solid electrolyte, represented by Li x K 2-x AgBiBr6(DMSO).
[0065] Operation steps S3-S4 need to be performed in an argon environment, and the water oxygen level is controlled below 0.2 ppm.
[0066] The electrolyte obtained in this example was prepared into a solid-state battery (see the performance test experiment below for the method). Its ionic conductivity is 2*10 -5 S / cm.
[0067] Performance testing experiment
[0068] Weigh 0.05 g of the electrolyte obtained in Examples 1, 2, 3 and Comparative Examples 1 and 2, pour it into a solid-state battery test mold with an inner diameter of 10 mm, and apply a pressure of 950 MPa on the press and maintain it for 10 minutes. Then, install the battery test mold into the fastening mold and fasten it with a torque wrench at a torque of 3.75 N m. Determine the AC impedance spectrum of the experimental system. The test principle of ionic conductivity is as shown in formula (I):
[0069]
[0070] In the formula, L is the thickness of the electrolyte sheet; A is the cross-sectional area in the test mold (in cm 2 ), the inner diameter of the mold is 10 mm, so the area A is 0.78 cm 2 ; R b It is the horizontal coordinate value (unit Ω) at the intersection of the semicircle and the straight line of the impedance spectrum in the impedance test. Figure 4 middle. Figure 4 The ionic conductivity test results of solid-state batteries made of solid electrolytes of Examples 1, 2, 3 and Comparative Examples 1 and 2. x Cs 2-x The impedance value of NaInCl6(DMSO) is 800Ω, and the calculated ionic conductivity is 8*10 -5S / cm, which reaches the general standard of current halide solid electrolytes, and provides the possibility for the subsequent exploration of other types of new halide solid electrolytes.
Claims
1. A method for preparing a double perovskite solid electrolyte, characterized in that: First, a double perovskite-type A2B(Ⅰ)B(Ⅱ)X6 base material is synthesized, and then a lithium salt, a solvent and the base material are mixed by an ion exchange method to prepare a double perovskite-type solid electrolyte.
2. The method for preparing a double perovskite solid electrolyte according to claim 1, characterized in that: The specific steps include: S1. Weigh the salts, denoted as AX, B(Ⅰ)X, and B(Ⅱ)X, in a molar ratio of 1.5-2.5:0.5-1.5:1, mix them in an appropriate amount of water or HX solution, and heat and stir at 50-220°C for more than 15 minutes to obtain a mixed solution; Where A, B(Ⅰ), and B(Ⅱ) represent cations, respectively, and X represents anions; S2, separating the mixed liquid obtained in step S1 into solid and liquid, washing and drying, and obtaining a double perovskite-type substrate material A2B(Ⅰ)B(Ⅱ)X6; S3, mixing the double perovskite substrate material A2B(Ⅰ)B(Ⅱ)X6 obtained in step S2 with a solvent and an excess of lithium salt, and heating and stirring for more than 48 hours to perform ion exchange; S4, solid-liquid separation, washing and drying to obtain a double perovskite solid electrolyte.
3. The method for preparing a double perovskite solid electrolyte according to claim 2, characterized in that: In step S1, the anion X of the salt is a fluoride ion F - 、Chloride ion Cl - 、Br - 、Iodide ion I - 、cyanide ion CN - At least one of; and / or, in step S1, the cation in the halide salt AX is a potassium ion K + 、Rubidium ion Rb + , Cesium ion Cs + 、Silver ion Ag + 、Ti ion Ti 4+ 、Ammonium ion NH4 + 、Methylamine cation CH3NH3 + At least one of; and / or, in step S1, the cation in the halide salt B(I)X is a lithium ion Li + 、Sodium ion Na + Potassium ion K + 、Rubidium ion Rb + 、Silver ion Ag + 、Gold ion Au + 、Ti ion Ti 4+ 、Ammonium ion NH4 + At least one of; and / or, in step S1, the cation in the halide salt B(II)X is an aluminum ion Al 3+ 、Gallium ion Ga 3+ 、Indium ion In 3+ 、Ti ion Ti 3+ 、Antimony ion Sb 5+ 、Bi ion 5+ , at least one of transition metal elements; and / or, in step S1, the halide salts AX and B(Ⅰ)X belong to different types of halide salts.
4. The method for preparing a double perovskite solid electrolyte according to claim 2 or 3, characterized in that: In step S1, the amount of HX solute in the HX solution is more than 10 times the amount of the double perovskite substrate material A2B(Ⅰ)B(Ⅱ)X6; and / or, in step S1, water is deionized water, and the amount used is more than 10 times the amount of the double perovskite substrate material A2B(Ⅰ)B(Ⅱ)X6.
5. The method for preparing a double perovskite solid electrolyte according to claim 2 or 3, characterized in that: In step S3, the selected solvent can fully dissolve the lithium salt, but is insoluble or slightly soluble in the double perovskite-type substrate material A2B(Ⅰ)B(Ⅱ)X6.
6. The method for preparing a double perovskite solid electrolyte according to claim 2 or 3, characterized in that: In step S3, the solvent is one of alcohol, ether, ester, amide, carbonate, sulfide, sulfoxide, sulfone, sulfonamide, nitrile, dinitrile, phosphate, sulfite, and sulfate; and / or, in step S3, the anion of the lithium salt is at least one of bistrifluoromethylsulfonyl, bisfluorosulfonyl imide, hexafluorophosphate, hexafluoroborate, bisoxalatoborate, difluorooxalatoborate, fluorosulfonyl-trifluoromethanesulfonyl imide, bispentafluoroethanesulfonyl imide, perchlorate, trifluoropotassium sulfonate, nitrate, carbonate, sulfate, and chloride.
7. The method for preparing a double perovskite solid electrolyte according to claim 2 or 3, characterized in that: In step S3, the amount of the lithium salt substance is more than 1 times the amount of the double perovskite-type substrate material A2B(Ⅰ)B(Ⅱ)X6; the amount of the solvent substance is more than 5 times the amount of the lithium salt substance.
8. The method for preparing a double perovskite solid electrolyte according to claim 7, characterized in that: In step S3, the amount of the lithium salt is 5-8 times the amount of the double perovskite substrate material A2B(Ⅰ)B(Ⅱ)X6; the amount of the solvent is 20-50 times the amount of the lithium salt.
9. The method for preparing a double perovskite solid electrolyte according to claim 2 or 3, characterized in that: In step S3, the heating temperature is 50-220°C; and / or, step S3 and step S4 need to be performed in an argon environment, and the water oxygen is controlled below 0.2ppm.
10. An all-solid-state battery, characterized in that: A double perovskite solid electrolyte prepared by the preparation method according to any one of claims 1 to 9.